Evidence, Determinants, And Consequences Of Asset Price Bubbles: The Case Of Malaysia And Singapore - Gary , John Rangel (2010)
Asset price bubbles have been a phenomenon that has occurred for centuries. This phenomenon can result in a negative impact on a country’s economy during the build-up and collapse phase. The issue with a bubble build-up is the misallocation of scarce economic resources in speculative activities which crowd out investment in productive activities. When the bubble collapses, its effect is even greater on society as a whole. Researchers nevertheless are still debating its existence even historically, what its causes are, and whether it will has any consequential effects on countries generally and society at large. This study seeks to provide further insight on these three questions. A multi-test approach was employed to determine the existence of bubbles. Using the financial instability hypothesis proposed by Hyman Minsky and a polynomial distributed lag approach; several salient variables were identified to have explanatory properties on the propagation of asset price bubbles in Malaysia and Singapore. In the case of stock price bubbles propagation, both real GDP growth and capital flows are consistently significant explanatory variables. As for real estate bubbles, real interest rates, real GDP growth, and the stock market bubble proxy are leading indicators. With these leading indicators in hand, both investors and government authorities can implement appropriate monitoring measures on these salient variables to ameliorate the effects of bubble build-up and its collapse.